Oneiropoetics as a form of realization of the author's picture of the world in a literary fairy tale and fiction (Eurasian Journal of Philology Science and Education, 2023)
The article is devoted to the study of the dream motive in a literary fairy tale and an artistic work, its form as the embodiment of the author's worldview. As evidenced by the works of art, the oneiric element structures the author's plan; the dream motive opens the veil of the future, the secrets of the past. Dream motives are not uncommon in folklore and literature, and their analysis remains important for literary theory in structuring events in the past, present and future. The article covers such genres that were most often used by the authors as dream-revelation, dream-nightmare, dream-journey, etc. As materials for the study were the works of A. Zhaksylykov Dreams of the Damned and A. Altai Tusyk (Miscarriage), Tus (Orphan), which told about modern life realities, about the dichotomy of wealth and poverty, about vice and virtue, about finding ways out of social chaos. The methodology of the study includes the continuity of scientific approaches, the use of traditional and innovative methods of literary analysis: content analysis, comparative typological method, myth poetics and dream poetics (oneiropoetics), psychoanalysis. Based on the comparison of the dream motive, mythological motive and fairy tales, the position is justified that they are very close in content; they are revealed through general artistic form, causal and effect relationships, chronotope, supernatural, unrealistic narrative content, mental "dwelling" and rethinking of the situation, etc. The motive of the dream is archetypal and is one of the most important structural elements of a literary work.